1988
DOI: 10.1103/physrevlett.61.82
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Solitary Waves and Weak Double Layers in the Magnetospheric Plasma

Abstract: The wave experiment of the Viking satellite frequently detected dynamic small-scale (=100 m), large-amplitude, rarefactive (~An/n ( &50%) solitary waves of negative potential (~|S~& 2 V) moving upwards along the magnetic field lines (v =5 to & 50 km/s). The structures, which resemble ion holes, often have an upward-directed net potential drop (& l V) and are then interpreted as weak double layers. PACS numbers: 52.35.Mw, 52.35.gz, 52.35.Sb, 52.70.Ds There is currently an interest in the appearance in space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
211
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(226 citation statements)
references
References 19 publications
14
211
1
Order By: Relevance
“…This result was based upon Langmuir probe sweeps near the ion beams which inferred a 1-10 eV temperature for the electrons [Bostrom et at., 1988]. However, Hilgers et al [1992] show that the Viking Langmuir probe current is dominated by photoelectrons from the wire boom within ion beam regions.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was based upon Langmuir probe sweeps near the ion beams which inferred a 1-10 eV temperature for the electrons [Bostrom et at., 1988]. However, Hilgers et al [1992] show that the Viking Langmuir probe current is dominated by photoelectrons from the wire boom within ion beam regions.…”
Section: Observationsmentioning
confidence: 99%
“…No mass separation was performed and the cold ions were assumed to be hydrogen. A cold electron (few eV) component with roughly the same density, as required for charge neutrality, was inferred from Langmuir probe measurements [Bostrom et at., 1988; Koskinen et at., 1989]. These Viking observations were made at 8000-11000 km altitudes, in the afternoon-evening sector and in a region whose total accelerating potential was about 1 kV.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite measurements of the high-frequency electric field have revealed the existence of electrostatic ion-cyclotron waves (EICW) and of solitary waves, also named double layers (DL), in which the potential can jump parallel to B by a good fraction of kT e over scales of the order of 10 Debye lengths, X D (Temerin et al 1982;Bostrom et al 1988). The postulated anomalous resistivity may thus be distributed (EICW) or concentrated in a multitude of small ion-acoustic double layers (DL).…”
Section: Microphysicsmentioning
confidence: 99%
“…Other evidences of accelerated electrons, with broader distributions in energy and direction, have shown the importance of time-varying electric fields [Hultqvist et al, 1988], possibly carried by Alfvén waves [Kletzing, 1994]. Deep plasma cavities above the Earth auroral zone are a privileged place for electron acceleration [Hilgers et al, 1992] and the subsequent turbulence, characterized by electrostatic coherent structures such as double layers and solitary waves [Bostrom et al, 1988;Eriksson et al, 1997]. With the Freja spacecraft, is was shown that these regions are pervaded by Alfvén wave packets (termed as Solitary Kinetic Alfvén Waves, SKAW).…”
Section: Introductionmentioning
confidence: 99%